Filtração de ceras aplicando diferentes tratamentos físicos na superfície de meios filtrantes - Missau, Juliano (2017)
The presence of inorganic substances in the composition of crude wax decreases its commercial value, requiring purification of the product. A new physical treatment on the surface of the filter media was carried out by applying the Nylon-6 nanofibers in the untreated para aramid filter. Forcespinning equipment was used in the production of nanofibers using the centrifuge technique. The performance of the nanofiber-covered filter was compared with the results obtained for other types of surface treatment of filter media of the same composition (nonwoven para aramid fiber fabric), one without physical treatment, and another treated using singeing. An experimental design was carried out to find the optimum operating temperature and pressure (170 °C and 2.5 bar, respectively). The filtrate volume, specific resistance of the filter cake, and filter medium resistance were determined keeping the filtration time, temperature, and pressure constant at 1 h, 170 ºC, and 2.5 bar, respectively. The nanofiber-covered filter showed the best performance among the studied surfaces, providing a higher wax filtrate volume and greater retention of inorganics, with values of 5.39x10-5 m3 and 99.6%, respectively.